DESKRIPSI PROSES PEMBELAJARAN DI TAMAN KANAK-KANAK - Wijaya, Ivander Daniel (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
Kindergarten has an important role, because one of their main principle is to prioritize the child needs to develop and maximaze their growth and development. Kindergarten need to use the correct learning soit will appropriate with the child needs. This activity can be done with a play activity, because with playing can teach the child in many aspect, cognitive, motoric, language, and social emotion. This research want to see the learning materials related the cognitive, language, motoric and social emotion and want to see the application of play activity in the lesson process. The subject in this research is 1 teacher from non-private kindergarten and 2 teachers from private kindergarten at Surabaya. The data will be analize on descriptive from the observation and interview data. The result show that the teachers already understand about the important of applying the development aspect at the kindergarten. But, from the observation shows that mostly the given lesson material still focus only at the cognitive and soft motoric aspect, while the language, rough motoric and the social emotion not really seen. The material mostly using the paper and pecil. The teachers already know the important of playing activity but the implementation are not look dominantly. The dominant play activity are the constructive play activity.